Ukrainian period of Dziga Vertov’s creative work - Myslavskyi, Volodymyr; Chmil, Hanna; Bezruchko, Oleksandr; Cherkasova, Nataliia (КНУКіМ, 2021)
The objective of this study is to analyze the outcomes of Dziga Vertov’s conceptual search based on his works, The Eleventh Year (1928) and The Man with a Movie Camera (1929), which became the most remarkable documentaries in the Soviet cinematography. The authors also go into the reasons of diametrically opposite reviews of the critics on these films. This chapter of collective monograph is based on little-known critical publications about these films in the Ukrainian and Russian media in the 1920s.
Keywords: кіномистецтво українське радянське